Negative electrode current collector and preparation method thereof, sodium secondary battery, and electrical equipment

By using modified carbon materials and bifunctional additives in the functional layer of the negative electrode current collector, the problems of uneven sodium deposition and short cycle life in sodium-ion batteries are solved, achieving higher energy density and longer cycle life.

CN117727949BActive Publication Date: 2025-01-21SHENZHEN HITHIUM ENERGY STORAGE CONTROL TECHNOLOGY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410171661.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-07
Publication Date
2025-01-21
Estimated Expiration
2044-02-07

AI Technical Summary

Technical Problem

The overall energy density of sodium ion batteries is small, and the deposition of sodium metal on the negative electrode current collector is uneven, which easily forms sodium dendrites, reducing the cycle life of the battery.

Method used

Modified carbon materials are used as the functional layer of the negative electrode current collector. The modified carbon materials include carbon main materials and bifunctional additives. The bifunctional additives have sodium-loving and sodium-replenishing abilities, store sodium ions through embedding and adsorption, and reduce sodium deposition. nucleation overpotential.

Benefits of technology

The uniformity of sodium deposition is improved, the risk of sodium dendrite formation is reduced, the cycle life of the battery is extended, and the Coulombic efficiency of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117727949B_ABST
    Figure CN117727949B_ABST
Patent Text Reader

Abstract

The present application proposes a negative electrode current collector and a preparation method thereof, a sodium secondary battery, and an electrical device. The negative electrode current collector includes a substrate; a functional layer, wherein the functional layer is arranged on at least one side of the substrate, and the functional layer includes a modified carbon material, wherein the modified carbon material includes a carbon main material and a bifunctional additive, wherein the bifunctional additive is dispersed in the carbon main material, and the bifunctional additive includes R1-R2-Na, wherein R1 includes at least one of an alkyl group, a hydrogen atom, and an aromatic group, and R2 includes at least one of a carboxyl group, a carbonyl group, and an oxygen atom.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular, to a negative electrode current collector and a preparation method thereof, a sodium secondary battery, and electrical equipment. Background Art

[0002] Due to the abundance of sodium resources, sodium-ion batteries have been regarded as an important supplement to lithium batteries in the low-cost field. However, the current overall energy density of sodium-ion batteries is relatively small, much lower than that of lithium-ion batteries. Since the theoretical specific capacity of metallic sodium is relatively high, using metallic sodium as the negative electrode is an effective solution to increase the energy density. During the first charge and discharge of negative electrode-free sodium batteries, metallic sodium will be deposited on the negative electrode current collector to form. During the deposition process, the sodium deposition is uneven, and it is easy for sodium dendrites to grow disorderly on the surface of the negative electrode current collector, increasing the risk of damaging the electrolyte interface film and reducing the cycle life of the battery. Summary of the invention

[0003] The present application aims to solve one of the technical problems in the related art at least to some extent.

[0004] In one aspect of the present application, a negative electrode current collector is proposed, the negative electrode current collector includes a substrate; a functional layer, the functional layer is arranged on at least one side of the substrate, the functional layer includes a modified carbon material, the modified carbon material includes a carbon main material and a bifunctional additive, the bifunctional additive is dispersed in the carbon main material, and the bifunctional additive includes R1-R2-Na, wherein R1 includes at least one of an alkyl group, a hydrogen atom, and an aromatic group, and R2 includes at least one of a carboxyl group, a carbonyl group, and an oxygen atom. Thus, the bifunctional additive has both sodium affinity and sodium supplementation capabilities, which can reduce the nucleation overpotential of sodium deposition and improve the uniformity of sodium deposition. At the same time, when the total amount of sodium ions reversibly stored between the positive and negative electrodes is reduced, the sodium supplementation effect can be exerted to improve the coulombic efficiency and cycle life of the battery.

[0005] Optionally, R1 includes an alkyl group with 1 to 3 carbon atoms, and R2 includes at least one of a carboxyl group and an oxygen atom. Thus, the dissolution effect of the bifunctional additive in the solvent is improved, the utilization rate of the bifunctional additive is improved, and the cost of the bifunctional additive is reduced.

[0006] Optionally, at least one of a C-Na ionic bond and a COC covalent bond exists between the carbon main material and the bifunctional additive. Thus, there is a strong intermolecular force between the carbon main material and the bifunctional additive, which can improve the adhesion of the bifunctional additive in the carbon main material and reduce the risk of the bifunctional additive falling off during the charge and discharge process.

[0007] Optionally, the thickness of the functional layer is 0.2 μm-10 μm. Thus, the sodium supplementation and sodium affinity sites on the negative electrode current collector are increased, the sodium supplementation and sodium affinity effects of the bifunctional additive are improved, and the coulombic efficiency and cycle life of the battery are improved.

[0008] Optionally, based on the total mass of the functional layer, the mass proportion of the modified carbon material is 70%-99%. The modified carbon material stores sodium ions by embedding and adsorption. The pre-sodiumization behavior is beneficial to reduce the nucleation overpotential of sodium deposition, improve the sodium affinity of the negative electrode current collector, improve the sodium supplementation effect, and thus improve the coulombic efficiency and cycle life of the battery.

[0009] Optionally, in the modified carbon material, the mass proportion of the carbon main material is 50%-98%, and the mass proportion of the bifunctional additive is 2%-50%. Thus, the carbon main material provides a uniform and stable loading site for the bifunctional additive. By making the content of the carbon main material and the bifunctional additive within the above range, more loading sites for the bifunctional additive can be formed on the functional layer, thereby improving the adhesion of the bifunctional additive in the carbon main material, and at the same time improving the sodium affinity and sodium supplementation effect of the bifunctional additive, thereby improving the coulombic efficiency and cycle life of the battery.

[0010] Optionally, the main carbon material includes at least one of carbon black, carbon fiber, carbon nanotube, and graphene.

[0011] Optionally, the bifunctional additive includes at least one of sodium formate, sodium acetate, and sodium benzoate. Thus, the bifunctional additives of the above types have both sodium replenishing and sodium affinity capabilities, thereby improving the uniformity of sodium deposition, and when the total amount of sodium ions reversibly stored between the positive and negative electrodes is reduced, the sodium replenishing effect can be exerted, thereby improving the coulombic efficiency and cycle life of the battery.

[0012] Optionally, the functional layer further comprises a binder, and based on the total mass of the functional layer, the mass proportion of the binder is 1%-30%, thereby improving the bonding force between the functional layer and the substrate.

[0013] The second aspect of the present application provides a method for preparing the negative electrode current collector of the first aspect of the present application, comprising: forming a functional layer on at least one side of a substrate, the functional layer comprising a carbon material and a bifunctional additive, the functional layer comprising a modified carbon material, the modified carbon material comprising a carbon main material and a bifunctional additive, the bifunctional additive being dispersed in the carbon main material, and the bifunctional additive comprising R1-R2-Na, wherein R1 comprises at least one of an alkyl group, a hydrogen atom, and an aromatic group, and R2 comprises at least one of a carboxyl group, a carbonyl group, and an oxygen atom. Thus, the method can improve the sodium affinity and sodium supplementation ability of the negative electrode current collector, thereby improving the uniformity of sodium deposition of the negative electrode current collector, reducing the risk of generating sodium dendrites, and at the same time, when the total amount of sodium ions reversibly stored between the positive and negative electrodes is reduced, the sodium supplementation effect can also be exerted, thereby improving the coulombic efficiency and cycle life of the battery.

[0014] Optionally, the method for forming the functional layer includes: mixing the carbon main material and the bifunctional additive, and heat treating to obtain a modified carbon material; mixing the modified carbon material with a solvent to form a slurry, forming it on at least one side of the substrate, and drying to obtain the functional layer. Thus, a strong intermolecular force is formed between the carbon main material and the bifunctional additive, improving the adhesion of the bifunctional additive to the carbon main material and reducing the risk of the bifunctional additive falling off during the charge and discharge process.

[0015] Optionally, the heat treatment temperature is 50°C-250°C, and the heat treatment time is 0.1h-24h. Thus, through heat treatment, C-Na ionic bonds and COC covalent bonds can be formed between the carbon main material and the bifunctional additive, thereby improving the adhesion of the bifunctional additive in the carbon main material and reducing the probability of thermal decomposition of the bifunctional additive.

[0016] Optionally, the modified carbon material, the binder and the solvent are mixed, thereby improving the bonding force between the functional layer and the substrate.

[0017] The third aspect of the present application provides a sodium secondary battery, comprising the negative electrode current collector provided in the first aspect of the present application or the negative electrode current collector prepared by the method provided in the second aspect of the present application, wherein after the first charge and discharge of the sodium secondary battery, metallic sodium is deposited on the side of the functional layer away from the substrate. Thus, the coulombic efficiency and cycle life of the sodium secondary battery can be improved.

[0018] The fourth aspect of the present application provides an electrical device, including the sodium secondary battery provided by the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0020] Figure 1 A schematic diagram of the structure of a negative electrode current collector according to an embodiment of the present application is shown.

[0021] Figure 2 A schematic diagram of the process of preparing a negative electrode current collector according to an embodiment of the present application is shown.

[0022] Reference numerals:

[0023] 10: negative electrode current collector; 11: substrate; 12: functional layer. DETAILED DESCRIPTION

[0024] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0025] In one aspect of the present application, a negative electrode current collector is provided, referring to Figure 1 , the negative electrode current collector 10 includes a substrate 11; a functional layer 12, the functional layer 12 is arranged on at least one side of the substrate 11, the functional layer 12 includes a modified carbon material, the modified carbon material includes a carbon main material and a bifunctional additive, the bifunctional additive is dispersed in the carbon main material, and the bifunctional additive includes R1-R2-Na, wherein R1 includes at least one of an alkyl group, a hydrogen atom, and an aromatic group, and R2 includes at least one of a carboxyl group, a carbonyl group, and an oxygen atom. Thus, the bifunctional additive has both sodium affinity and sodium supplementation capabilities, which can reduce the nucleation overpotential of sodium deposition and improve the uniformity of sodium deposition. At the same time, when the total amount of sodium ions reversibly stored between the positive and negative electrodes is reduced, the sodium supplementation effect can be exerted to improve the coulombic efficiency and cycle life of the battery.

[0026] The following is a detailed description of the principle by which the present application can achieve the above beneficial effects:

[0027] The negative electrode current collector 10 proposed in the present application includes a functional layer 12, and the functional layer 12 includes a bifunctional additive R1-R2-Na, wherein the R2 group has a certain electron-withdrawing ability and has a strong electrostatic interaction with sodium ions, which can improve the binding force between the metal layer formed by sodium deposition and the functional layer 12 during sodium deposition, reduce the nucleation overpotential and polarization potential of sodium deposition, improve the uniformity and density of sodium deposition, reduce the probability of generating sodium dendrites, reduce the risk of the diaphragm being pierced by sodium dendrites and causing battery short circuit, and improve the cycle life of the battery; at the same time, when the total amount of sodium ions reversibly stored between the positive and negative electrodes is reduced, the Na component in the bifunctional additive can play a sodium supplementing ability and improve the coulombic efficiency of the battery. In order to provide a uniform and stable loading site for the bifunctional additive on the surface of the substrate 11, the bifunctional additive is dispersed in the carbon main material to reduce the probability of agglomeration of the bifunctional additive, thereby improving the uniformity of the distribution of the bifunctional additive in the functional layer 12 and further improving the uniformity of sodium deposition. At the same time, modified carbon materials can store sodium ions by embedding and adsorption for pre-sodiumization, which is beneficial to reduce the nucleation overpotential of sodium deposition, improve the sodium affinity of the negative electrode current collector, improve the sodium replenishment effect, and thus improve the coulombic efficiency and cycle life of the battery.

[0028] According to some embodiments of the present application, R1 may include an alkyl group of 1 to 3 carbon atoms, and R2 may include at least one of a carboxyl group or an oxygen atom. Thus, the solubility of the bifunctional additive in the solvent is improved, the utilization rate of the bifunctional additive is improved, and the cost of the bifunctional additive is reduced. According to some specific embodiments of the present application, the bifunctional additive includes at least one of sodium formate, sodium acetate, and sodium benzoate.

[0029] According to some embodiments of the present application, the functional layer 12 is disposed on at least one surface of the substrate 11 .

[0030] According to some embodiments of the present application, based on the total mass of the functional layer 12, the mass proportion of the modified carbon material can be 70%-99%. For example, it can be 70%, 75%, 80%, 85%, 90%, 95% or 99%, etc., or it can be a range composed of any of the above numerical values. The modified carbon material stores sodium ions by embedding and adsorption. The pre-sodiumization behavior is beneficial to reduce the nucleation overpotential of sodium deposition, improve the sodium affinity and sodium supplementation effects of the bifunctional additive, and thus improve the coulombic efficiency and cycle life of the battery. If the mass proportion of the modified carbon material is too small, too much non-conductive binder will hinder the electron / ion transport in the functional coating and affect the sodium deposition / stripping process.

[0031] According to some embodiments of the present application, in the modified carbon material, the mass proportion of the carbon main material can be 50%-98%, and the mass proportion of the dual-functional additive can be 2%-50%.

[0032] Specifically, the mass proportion of the carbon main material can be 50%, 60%, 70%, 80%, 90% or 98%, etc., or can be a range composed of any of the above values. Thus, by making the mass proportion of the carbon main material within the above range, more, more uniform, and more stable loading sites can be provided for the bifunctional additive on the surface of the substrate 11, thereby improving the uniformity of the distribution of the bifunctional additive in the functional layer 12, improving the uniformity of the sodium affinity of each region of the functional layer 12, and then improving the uniformity of sodium deposition, and improving the cycle life of the battery. If the content of the carbon main material is too much, too little additive is not enough to form a sodium affinity site in the modified carbon material, and the sodium nucleation overpotential is high; if the content of the carbon main material is too little, too much non-conductive additive will hinder the electron transport of the modified carbon material and reduce the reversibility of the sodium deposition / stripping process.

[0033] Specifically, the mass proportion of the bifunctional additive can be 2%, 10%, 20%, 30%, 40% or 50%, etc., or can be a range composed of any of the above values. Thus, on the basis of uniform distribution of the bifunctional additive in the functional layer, the sodium affinity and sodium replenishment ability of the negative electrode current collector 10 can be further improved, thereby improving the coulombic efficiency and cycle life of the battery. If the content of the bifunctional additive is too little, it is not enough to form a sodium affinity site in the modified carbon material, and the sodium nucleation overpotential is high; if the content of the non-conductive bifunctional additive is too much, it will hinder the electron transport of the modified carbon material and reduce the reversibility of the sodium deposition / stripping process.

[0034] According to some embodiments of the present application, the average particle size of the bifunctional additive is 5nm-100nm. For example, it can be 5nm, 10nm, 30nm, 50nm, 70nm, 90nm or 100nm, etc., or it can be a range composed of any of the above numerical values. Thus, the average particle size of the bifunctional additive is relatively small, which is conducive to the uniform distribution of the bifunctional additive in the functional layer, thereby improving the uniformity of the distribution of the bifunctional additive in the functional layer 12, thereby improving the uniformity of the sodium affinity of each region of the functional layer 12, improving the uniformity of sodium deposition, reducing the probability of local generation of sodium dendrites, reducing the risk of short circuit caused by puncture of the diaphragm, and thus improving the cycle life of the battery. If the average particle size of the bifunctional additive is too large, the uniformity of the distribution of the bifunctional additive in the functional layer will be reduced to a certain extent.

[0035] According to some embodiments of the present application, the main carbon material may include at least one of carbon black, carbon fiber, carbon nanotube, and graphene.

[0036] According to some embodiments of the present application, the functional layer 12 may further include a binder, and the mass proportion of the binder is 1%-30% based on the total mass of the functional layer 12. Thus, the binder can improve the bonding force between the functional layer 12 and the substrate 11 and reduce the risk of the functional layer 12 falling off.

[0037] Specifically, the mass proportion of the binder can be 1%, 5%, 10%, 15%, 20%, 25% or 30%, etc., or can be a range composed of any of the above values. Thus, by making the mass proportion of the binder within the above range, while improving the bonding force between the functional layer 12 and the substrate 11, the effect of the binder on the conductivity of the functional layer 12 is reduced. If the content of the binder is too much, the excessive non-conductive binder will hinder the electron / ion transport in the functional coating and affect the sodium deposition / stripping process.

[0038] As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polyacrylonitrile, polyimide, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, sodium polyacrylate, sodium alginate, polytetrafluoroethylene, and polyvinyl alcohol.

[0039] According to some embodiments of the present application, the thickness of the functional layer 12 may be 0.2 μm-10 μm. For example, it may be 0.2 μm, 1 μm, 3 μm, 5 μm, 7 μm, 9 μm or 10 μm, etc., or may be a range composed of any of the above numerical values. Thus, by making the thickness of the functional layer 12 within the above range, the number of sodium-philic and sodium-supplementing sites can be increased, thereby improving the uniformity of sodium deposition. At the same time, the transmission rate of the electrolyte on the negative electrode current collector 10 is increased, and the wettability of the electrolyte to the negative electrode current collector 10 is improved. By making the thickness of the functional layer 12 within the above range, the risk of the functional layer 12 falling off due to the functional layer 12 being too thick can also be reduced. If the thickness of the functional layer is too small, the number of sodium-philic and sodium-replenishing sites on the surface of the substrate is small, which will affect the sodium-philic and sodium-replenishing effects of the bifunctional additive to a certain extent, and further affect the uniformity of sodium deposition; if the thickness of the functional layer is too large, that is, the distance from the surface of the functional layer to the surface of the substrate is large, the electron / ion transmission distance will be increased, affecting the rate performance of the battery; moreover, if the thickness of the functional layer is too large, the bonding force between the functional layer and the substrate will be reduced to a certain extent, increasing the risk of the functional layer falling off and poor electrolyte wettability.

[0040] The second aspect of the present application provides a method for preparing the negative electrode current collector 10 of the first aspect of the present application, comprising: forming a functional layer 12 on at least one side of a substrate 11, the functional layer 12 comprising a carbon material and a bifunctional additive, the functional layer 12 comprising a modified carbon material, the modified carbon material comprising a carbon main material and a bifunctional additive, the bifunctional additive being dispersed in the carbon main material, and the bifunctional additive comprising R1-R2-Na, wherein R1 comprises at least one of an alkyl group, a hydrogen group, and an aromatic group, and R2 comprises at least one of a carboxyl group, a carbonyl group, and an oxygen group. Thus, the method can improve the sodium affinity and sodium supplementation ability of the negative electrode current collector 10, thereby improving the uniformity of sodium deposition of the negative electrode current collector 10, reducing the risk of generating sodium dendrites, and at the same time, when the total amount of sodium ions reversibly stored between the positive and negative electrodes is reduced, the sodium supplementation effect can also be exerted, thereby improving the coulombic efficiency and cycle life of the battery.

[0041] According to some embodiments of the present application, reference Figure 2 , the method may include:

[0042] S100: Formation of modified carbon materials

[0043] Specifically, the carbon main material and the dual-functional additive are mixed and heat-treated to obtain a modified carbon material.

[0044] According to some embodiments of the present application, the temperature of the heat treatment may be 50°C-250°C, for example, 50°C, 100°C, 150°C, 200°C or 250°C, etc., or may be a range composed of any of the above numerical values; the time of the heat treatment may be 0.1h-24h, for example, 0.1h, 1h, 5h, 10h, 15h, 20h or 24h, etc., or may be a range composed of any of the above numerical values. Thus, by heat treating the carbon main material and the bifunctional additive, a strong C-Na ionic bond and COC covalent bond may be formed between the carbon main material and the bifunctional additive, thereby improving the adhesion of the bifunctional additive in the carbon main material and reducing the risk of the bifunctional additive falling off during the charge and discharge process. By making the temperature and time of the heat treatment within the above range, the probability of thermal decomposition of the bifunctional additive can also be reduced, thereby improving the stability of the bifunctional additive. If the heat treatment temperature is too low or the time is too short, the interaction force between the carbon main material and the bifunctional additive is weak, which will reduce the adhesion of the bifunctional additive in the carbon main material to a certain extent and increase the risk of the bifunctional additive falling off in the carbon main material; if the heat treatment temperature is too high or the time is too long, the probability of decomposition of the bifunctional additive will increase to a certain extent.

[0045] According to some embodiments of the present application, the temperature of the heat treatment may be 80°C-200°C.

[0046] S200 : Mixing the modified carbon material with a solvent to form a slurry, forming the slurry on at least one side of the substrate 11 , and drying the slurry to obtain the functional layer 12 .

[0047] According to some embodiments of the present application, the solvent may be N-methylpyrrolidone or deionized water.

[0048] According to some embodiments of the present application, the slurry may be coated on at least one surface of the substrate 11 , and the negative electrode current collector 10 may be obtained through baking and rolling.

[0049] As an example, the coating method includes at least one of transfer coating, extrusion coating or gravure coating.

[0050] As an example, when the sodium secondary battery is a sodium metal battery, the substrate 11 of the negative electrode current collector 10 may be sodium metal.

[0051] As an example, when the sodium secondary battery is a negative electrode-free sodium battery, the substrate 11 of the negative electrode current collector 10 may be a metal foil, a porous metal plate, a porous carbon material or a composite current collector. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate 11. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate 11 (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.) on a substrate 11.

[0052] According to some specific embodiments of the present application, the substrate 11 of the negative electrode current collector 10 may be aluminum.

[0053] As an example, during the process of forming the slurry, mechanical stirring or ball milling stirring can be performed to improve the uniformity of the slurry.

[0054] According to some embodiments of the present application, the modified carbon material, the binder and the solvent may be mixed to form a slurry, thereby improving the bonding force between the functional layer 12 and the substrate 11 .

[0055] The third aspect of the present application provides a sodium secondary battery, comprising the negative electrode current collector 10 provided in the first aspect of the present application or the negative electrode current collector 10 prepared by the method provided in the second aspect of the present application, wherein after the first charge and discharge, the sodium secondary battery deposits metallic sodium on the side of the functional layer 12 away from the substrate 11. Thus, the coulombic efficiency and cycle life of the sodium secondary battery can be improved.

[0056] As an example, the sodium secondary battery may be a sodium metal battery or a negative electrode-less sodium battery.

[0057] According to some embodiments of the present application, the sodium secondary battery further includes a positive electrode sheet and a separator, and the separator is disposed between the positive electrode sheet and the negative electrode current collector.

[0058] The positive electrode sheet includes a positive current collector and a positive active material layer formed on the positive current collector, and the positive active material layer includes a positive active substance, a positive binder and a positive conductor. In the embodiment of the present application, the positive current collector can be made of a material with good conductivity and mechanical strength, preferably aluminum foil.

[0059] In the embodiments of the present application, the specific types of positive electrode active materials are not particularly limited, and those skilled in the art can select them according to actual needs. As some specific examples, the positive electrode active materials include at least one of sodium vanadium phosphate, sodium vanadium fluorophosphate, sodium iron phosphate, sodium iron pyrophosphate and composite sodium iron phosphate.

[0060] In the embodiments of the present application, the specific type of the positive electrode conductive agent is not particularly limited, and those skilled in the art can select it according to actual needs. As some specific examples, the positive electrode conductive agent includes at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0061] Likewise, the specific type of the positive electrode binder is not particularly limited, and those skilled in the art may select it according to actual needs. As some specific examples, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).

[0062] The preparation method of the positive electrode plate includes: mixing the positive electrode active material, the positive electrode binder and the positive electrode conductive agent evenly according to a preset ratio, adding a solvent and stirring evenly to form a positive electrode slurry, then coating it on the current collector, drying it, and finally cutting it into a specific shape of positive electrode plates for use according to the different battery shells.

[0063] The fourth aspect of the present application provides an electrical device, including the sodium secondary battery provided by the third aspect of the present application.

[0064] Specifically, the electrical equipment may be, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc. Electric toys may include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.

[0065] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.

[0066] Example 1

[0067] 1. Preparation of negative electrode current collector

[0068] The carbon fiber and sodium formate were mixed in a mass ratio of 80:20, heated to 150° C. for 5 h to obtain a modified carbon material.

[0069] The modified carbon material and the binder were mixed with the solvent N-methylpyrrolidone in a mass ratio of 70:30 and stirred into a uniform slurry with a solid content of 3%. The slurry was coated on an aluminum foil using a coater and dried in an oven. The current collector was cold pressed using a roller press to obtain a functional layer with a thickness of 1 μm.

[0070] 2. Preparation of positive electrode sheet

[0071] The active material (sodium vanadium phosphate), conductive agent (ketjen black), and binder (PVDF) are mixed evenly in a stirring device at a mass ratio of 90:3:7, and then a certain amount of solvent (nitromethyl pyrrolidone) is added and stirred to form a uniform slurry with a solid content of 40%. The slurry is coated on the positive electrode current collector aluminum foil using a coating machine, dried, and cold pressed to obtain a positive electrode sheet.

[0072] 3. Prepare electrolyte

[0073] In an argon-protected glove box, take 1 L of diethylene glycol dimethyl ether into a volumetric flask; weigh 168 g of sodium hexafluorophosphate and dissolve it in the above solvent; stir thoroughly until the sodium salt is completely dissolved to obtain the desired electrolyte.

[0074] 4. Diaphragm

[0075] A 16 μm polyethylene film was used as the separator.

[0076] 5. Assemble half-cell

[0077] Use a circular hole slicer to punch out the positive electrode sheet, negative electrode current collector, and separator into small discs of different diameters; put the negative electrode current collector, separator, and metal sodium sheet into the button battery shell in order, with the separator between the negative electrode current collector and the metal sodium sheet, add the above-mentioned electrolyte, and assemble into a button half-cell.

[0078] 6. Assemble the full battery

[0079] The positive electrode sheet, separator, and negative electrode current collector are stacked in order, with the separator located between the positive electrode sheet and the negative electrode current collector, and the above-mentioned electrolyte is added to assemble a full battery.

[0080] The preparation methods of the batteries in Examples 2 to 20 and Comparative Examples 1 to 4 are the same as those in Example 1, and the differences are detailed in Table 1.

[0081]

[0082]

[0083] Performance Testing

[0084] 1. Test methods for polarization potential and nucleation overpotential

[0085] The half-cell was subjected to constant current charge and discharge test on the battery charge and discharge tester; the charge and discharge currents were both set to 2 mA / cm 2 , the discharge cut-off capacity is set to 2 mAh / cm 2 , the charging cut-off voltage is set to 1.5 V; draw the 10th charge and discharge curve of the battery, and read its sodium nucleation overpotential, which is the sodium deposition nucleation overpotential of the negative electrode current collector; draw the 10th charge and discharge curve of the battery, and calculate its charge and discharge polarization potential, which is the polarization potential of the negative electrode current collector.

[0086] 2. Test method for first discharge specific capacity

[0087] The full battery was subjected to constant current charge and discharge test on a battery charge and discharge tester; based on the mass of the positive electrode active material, the charge and discharge current density was set to 100 mA / g, and the charge and discharge voltage range was set to 2.5V-3.8V. The discharge capacity of the first cycle is the first discharge capacity of the battery.

[0088] 3. Test method for 100-cycle capacity retention rate

[0089] The full battery was subjected to constant current charge and discharge test on a battery charge and discharge tester; based on the mass of the positive electrode active material, the charge and discharge current density was set to 100 mA / g, and the charge and discharge voltage range was set to 2.5V-3.8V. The ratio of the 100th cycle / 1st cycle discharge capacity is the 100-cycle cycle capacity retention rate.

[0090] 4. Test method for 100-cycle average coulomb efficiency

[0091] The full battery was subjected to constant current charge and discharge test on a battery charge and discharge tester; based on the mass of the positive electrode active material, the charge and discharge current density was set to 100 mA / g, and the charge and discharge voltage range was set to 2.5V-3.8V. The average value of the coulomb efficiency from the 1st to the 100th cycle is the 100-cycle average coulomb efficiency.

[0092] 5. Test method for thickness of functional layer

[0093] Take the plain foil used in the above embodiment and measure its thickness (T0) using a thickness gauge; take the negative electrode current collector coated with a functional coating on both sides prepared in the above embodiment and measure its thickness (T1) using a thickness gauge; then the thickness of the functional layer T2=(T1-T0) / 2.

[0094] The test results of the batteries in Examples 1 to 20 and Comparative Examples 1 to 4 are shown in Table 2.

[0095]

[0096] As can be seen from Table 1 and Table 2, the functional layer of the negative electrode current collector in Examples 1 to 20 includes a modified carbon material, and the modified carbon material includes a carbon main material and a bifunctional additive. The negative electrode current collector in Comparative Example 1 is not provided with a functional layer, and the negative electrode current collector in Comparative Example 2 has a functional layer, but the functional layer only includes a carbon main material and a binder, and the negative electrode current collector in Comparative Example 3 has a functional layer, but the functional layer only includes a bifunctional additive and a binder. The negative electrode current collector in Comparative Example 4 has a functional layer, but the additive on the functional layer is different from the type of bifunctional additive proposed in this application. From the test results, it can be seen that the nucleation overpotential and polarization potential of sodium deposition in Examples 1 to 20 are lower than those in Comparative Examples 1 to 4, and the first discharge specific capacity, cycle capacity retention rate and coulomb efficiency of the battery in Examples 1 to 20 are higher than those in Comparative Examples 1 to 4. It can be seen that the present application can reduce the nucleation overpotential of sodium deposition, improve the first discharge specific capacity and cycle capacity retention rate of the battery, and thus improve the cycle life and coulombic efficiency of the battery by arranging a modified carbon material including both a carbon main material and a bifunctional additive on the functional layer.

[0097] It can be seen from the comparison between Examples 1 to 3 and Comparative Example 4 that the additive in Comparative Example 4 does not have the function of replenishing sodium, so the cycle capacity retention rate and coulombic efficiency are lower than those of Examples 1 to 3. The present application can improve the cycle life and coulombic efficiency of the battery by setting a bifunctional additive in the functional layer.

[0098] As can be seen from Examples 4 to 8, the present application can form C-Na ionic bonds and COC covalent bonds between the carbon main material and the bifunctional additive by adjusting the temperature of the heat treatment, thereby improving the adhesion of the bifunctional additive in the carbon main material, reducing the probability of thermal decomposition of the bifunctional additive, and thus improving the sodium affinity and sodium supplementation effects of the bifunctional additive, and improving the cycle life and coulombic efficiency of the battery. As can be seen from Examples 4 to 7 compared with Example 8, when the heat treatment temperature is too high, the bifunctional additive is at risk of decomposition, which will reduce the cycle capacity retention rate and coulombic efficiency of the battery to a certain extent.

[0099] It can be seen from Examples 9 to 13 that the present application can increase the content of the bifunctional additive on the negative electrode current collector by adjusting the thickness of the functional layer, thereby improving the sodium affinity and sodium supplementation effects of the bifunctional additive, and improving the cycle life and coulombic efficiency of the battery. It can be seen from the comparison between Examples 9 and 10 to 13 that if the thickness of the functional layer is too thin and the content of the bifunctional additive on the functional layer is low, the cycle capacity retention rate and coulombic efficiency of the battery will be reduced to a certain extent.

[0100] It can be seen from Examples 16 to 20 that the present application can reduce the nucleation overpotential and polarization potential of sodium deposition by adjusting the content of the bifunctional additive, and improve the cycle life and coulombic efficiency of the battery. It can be seen from Examples 17 to 19 compared with Example 16 that if the content of the bifunctional additive is too little, the sodium affinity and sodium supplementation effects will be reduced to a certain extent, and the cycle capacity retention rate and coulombic efficiency of the battery will be reduced; it can be seen from Example 20 compared with Examples 17 to 19 that if the content of the bifunctional additive is too much, the bifunctional additive is not conductive, and the polarization potential will be increased to a certain extent, affecting the transmission of electrons by the modified carbon material and affecting the reversibility of the sodium deposition / stripping process.

[0101] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0102] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0103] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A negative electrode current collector, characterized in that: include: Base material; A functional layer, wherein the functional layer is disposed on at least one side of the substrate, the functional layer comprises a modified carbon material, the modified carbon material comprises a carbon main material and a bifunctional additive, the bifunctional additive is dispersed in the carbon main material, at least one of a C-Na ionic bond and a COC covalent bond exists between the carbon main material and the bifunctional additive, the bifunctional additive comprises at least one of sodium formate, sodium acetate, and sodium benzoate, and in the modified carbon material, the mass proportion of the carbon main material is 50%-98%, and the mass proportion of the bifunctional additive is 2%-50%; The modified carbon material is prepared by the following method: The carbon main material and the bifunctional additive are mixed and heat treated at a temperature of 50° C. to 250° C. for a time of 0.1 h to 5 h or 10 to 24 h to obtain the modified carbon material; The thickness of the functional layer is 0.2 μm-1 μm or 7 μm-10 μm.

2. The negative electrode current collector according to claim 1, characterized in that: Based on the total mass of the functional layer, the mass of the modified carbon material accounts for 70%-99%.

3. The negative electrode current collector according to claim 1, characterized in that: The main carbon material includes at least one of carbon black, carbon fiber, carbon nanotube and graphene.

4. The negative electrode current collector according to claim 1, characterized in that: The functional layer further comprises a binder, and based on the total mass of the functional layer, the mass proportion of the binder is 1%-30%.

5. A method for preparing the negative electrode current collector according to any one of claims 1 to 4, characterized in that: include: The carbon main material and the bifunctional additive are mixed and heat treated, wherein the heat treatment time is 0.1h-5h or 10-24h, and the heat treatment temperature is 50°C-250°C, so as to obtain a modified carbon material, wherein the bifunctional additive is dispersed in the carbon main material, and the bifunctional additive includes at least one of sodium formate, sodium acetate, and sodium benzoate. In the modified carbon material, the mass proportion of the carbon main material is 50%-98%, and the mass proportion of the bifunctional additive is 2%-50%; the thickness of the functional layer is 0.2μm-1μm or 7μm-10μm; A functional layer is formed on at least one side of a substrate, wherein the functional layer includes the modified carbon material.

6. The method according to claim 5, characterized in that The method of forming the functional layer comprises: The modified carbon material is mixed with a solvent to form a slurry, which is formed on at least one side of the substrate and dried to obtain the functional layer.

7. The method according to claim 6, characterized in that The modified carbon material, the binder and the solvent are mixed.

8. A sodium secondary battery, characterized in that: The invention comprises the negative electrode current collector according to any one of claims 1 to 4 or the negative electrode current collector prepared by the method according to any one of claims 5 to 7, wherein metallic sodium is deposited on the side of the functional layer away from the substrate after the first charge and discharge of the sodium secondary battery.

9. An electrical device, characterized in that: Includes the sodium secondary battery according to claim 8.

Citation Information

Patent Citations

  • Negative pole piece of sodium ion battery, electrochemical device and electronic equipment

    CN114709368A

  • Negative active material and preparation method thereof, electrochemical device and electric equipment

    CN116779849A